The Hire-Purchase (Amendment) Act 1992 - Balan, P; Ramlah Mahmood, Nik (Journal of Malaysian and Comparative Law, 2019)
The Hire-Purchase (Amendment) Act 1992 (hereafter referred to as "the Amendment Act") came into force on 1st June 1992. It makes many significant amendments to the principal Act, the Hire-Purchase Act 1967 (hereafter referred to as "the principal Act"). This note attempts to discuss the said amendments.